Super-hydrophilic oil-water separation membrane as well as preparation method and application thereof

By loading TiO2 on the metal mesh and performing hydrothermal modification treatment, a super hydrophilic oil-water separation membrane was prepared, which solved the problems of low oil-water separation efficiency and high cost in the prior art, and achieved efficient and stable emulsified oil separation and low energy consumption separation process.

CN119281139AActive Publication Date: 2025-01-10INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411712542.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-10
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

When treating oil-containing wastewater, the oil-water separation efficiency is low, the cost is high, the process is complex, and secondary pollution is present, so it cannot cope with the challenge of increasing emissions.

Method used

The metal mesh membrane is calcined and loaded with TiO2 sol, and a super-hydrophilic oil-water separation membrane is prepared by hydrothermal modification. Combining physical and chemical methods, it simplifies operation, reduces the use of chemical reagents, and reduces energy consumption.

Benefits of technology

It achieves efficient separation of emulsified oil, has good chemical and mechanical stability, can operate stably for a long time under different environmental conditions, is simple to operate, environmentally friendly, and has low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281139A_ABST
    Figure CN119281139A_ABST
Patent Text Reader

Abstract

The invention provides a super-hydrophilic oil-water separation membrane and a preparation method and application thereof, and the preparation method comprises the following steps: (1) carrying out first calcination treatment on a metal mesh membrane to obtain a membrane base; (2) spin-coating the TiO2 sol on a film substrate, and then carrying out second drying treatment and second calcining treatment to obtain a TiO2-metal net composite film; and (3) immersing the TiO2-metal net composite membrane in alkali liquor for hydrothermal modification treatment, and cleaning to obtain the super-hydrophilic oil-water separation membrane. The oil-water separation membrane provided by the invention has super-hydrophilic and super-oleophobic properties, and can be used for treating emulsified oil which is difficult to separate; and the oil-water separation membrane has good chemical stability and mechanical stability, and can stably operate for a long time under different environmental conditions. In addition, the preparation method combines physical and chemical methods, is simple to operate, does not need additional chemical reagents, and is environment-friendly and low in energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of separation membranes, and relates to a super-hydrophilic oil-water separation membrane and a preparation method and application thereof, and specifically relates to a super-hydrophilic oil-water separation membrane for separating emulsified oil and a preparation method and application thereof. Background Art

[0002] Oily wastewater is one of the environmental pollutions that bothers researchers in today's society. Improper treatment will cause water deterioration, fish resource reduction, toxin enrichment and resource waste. The effective separation and treatment of oil-water emulsions has become an indispensable part of industrial production, energy extraction and urban management. The traditional methods of oil-water separation include chemical method, biological method, physical and chemical method and biochemical method. However, these methods have problems such as low efficiency, high cost, complex process and secondary pollution, and cannot cope with the increasing discharge of oily wastewater.

[0003] Oil-water separation membranes are usually composed of a supporting substrate and a special wettability surface coating. They are separation membranes that use the special wettability of the surface to achieve specific passage of oil or water phases. Superhydrophilic oil-water separation membranes have the advantages of high flux and easy cleaning in practical applications because their specific passage phase is water.

[0004] CN 116764458A discloses an oil-water separation membrane and its preparation method and application. The oil-water separation membrane is made of a polyvinylidene fluoride porous membrane after being treated with alkali and hydrophilic modified; the modifiers used in the hydrophilic modification are tannic acid and copper ions. The provided oil-water separation membrane uses the polyvinylidene fluoride porous membrane as a base membrane, firstly hydroxylates it with an alkali reagent, and then uses copper ions and tannic acid to construct a Cu with good hydrophilicity on the membrane surface. 2+ / TA coordination coating. The oil-water separation membrane provided by this patent has good hydrophilicity and specific hierarchical roughness, and has hydrophilicity / underwater superoleophobicity, and has good application prospects in the field of oily wastewater treatment. The alkali treatment and hydrophilic modification steps involved in the preparation process of this patent are relatively complicated, which increases the difficulty and cost of industrial application.

[0005] CN 116617881A discloses a biomimetic super-hydrophilic / underwater oleophobic MOF coating mesh and its application. The preparation method of the coating mesh is: firstly, the stainless steel mesh is cleaned and phosphated, and then a layer of MOF material is deposited on the mesh by electrodeposition. After calcination, the MOF coating mesh is hydrophilically modified with polyvinyl pyrrolidone to obtain a biomimetic super-hydrophilic / underwater oleophobic MOF coating mesh. The MOF coating mesh obtained in this patent exhibits good spreadability and rapid penetration performance to water, with a contact angle of 0° with water and a water passing rate of 2 drops / s, showing excellent super-hydrophilic performance. However, the preparation process of this invention is complicated in terms of the uniformity of the electrodeposited MOF material and the precise control of the calcination conditions, thereby affecting the water flux. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a super-hydrophilic oil-water separation membrane and a preparation method and application thereof, wherein the oil-water separation membrane has super-hydrophilic and super-oleophobic properties, and can handle emulsified oil that is difficult to separate; and the oil-water separation membrane has good chemical stability and mechanical stability, and can operate stably for a long time under different environmental conditions. In addition, the preparation method combines physical and chemical methods, is simple to operate, does not require the addition of additional chemical reagents, is environmentally friendly, and has low energy consumption.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a super hydrophilic oil-water separation membrane, the preparation method comprising the following steps:

[0009] (1) subjecting the metal mesh membrane to a first calcination treatment to obtain a membrane base;

[0010] (2) TiO 2 The sol is spin-coated on the film base obtained in step (1), and then subjected to a second drying treatment and a second calcination treatment to obtain TiO 2 -Metal mesh composite film;

[0011] (3) The TiO obtained in step (2) 2 -The metal mesh composite membrane is immersed in an alkaline solution for hydrothermal modification, and the super-hydrophilic oil-water separation membrane is obtained after cleaning.

[0012] In the present invention, TiO is loaded on the metal mesh film. 2 It can make TiO 2 - The metal mesh composite membrane has superhydrophilic and superhydrophobic properties, and can separate the dispersed oil in the oil-water mixture; and then the obtained superhydrophilic oil-water separation membrane is hydrothermally modified with an alkaline solution to have the ability to separate the emulsified oil in the oil-water mixture;

[0013] The super-hydrophilic oil-water separation membrane obtained by the preparation method provided by the present invention has excellent mechanical stability and chemical stability, can operate stably for a long time under different environmental conditions, and realizes efficient separation of emulsified oil; and the preparation method provided by the present invention combines physical methods and chemical methods, is simple to operate, does not require the addition of additional chemical reagents, is environmentally friendly, and has low energy consumption.

[0014] As a preferred technical solution of the present invention, the metal mesh in step (1) includes any one of a stainless steel mesh, a copper mesh or a titanium mesh, preferably a stainless steel mesh.

[0015] In the present invention, the metal mesh film in step (1) is preferably a stainless steel mesh film, because during the calcination process, alumina will form on the surface of the stainless steel mesh film, which can further increase the roughness of the mesh film surface and thus improve the film base and TiO 2 The binding force of the sol.

[0016] Preferably, the pore size of the metal mesh membrane in step (1) is 200-600 mesh, for example, it can be 200 mesh, 300 mesh, 400 mesh, 500 mesh or 600 mesh, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] In the present invention, the pore size of the metal mesh is 200-600 meshes. When the mesh size of the mesh increases, the pore size of the mesh gradually decreases, the flux decreases as the mesh size decreases, and the separation efficiency increases as the mesh size increases. When the mesh size is 200-600 meshes, a relatively balanced relationship between separation efficiency and flux can be achieved. If the pore size is too large, the flux of the resulting separation membrane will be too small, and the oil-water separation efficiency will be better; if the pore size is too small, the flux of the resulting separation membrane will be too large, thereby reducing the oil-water separation efficiency.

[0018] Preferably, the temperature of the first calcination treatment in step (1) is 700-800°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the time for the first calcination treatment in step (1) is 4 to 8 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] As a preferred technical solution of the present invention, step (1) further includes a cleaning treatment and a first drying treatment performed in sequence before the first calcination treatment.

[0021] Preferably, the cleaning treatment in step (1) comprises: ultrasonic washing for 10 minutes using 3% dilute hydrochloric acid, ethanol and deionized water in sequence.

[0022] Preferably, the temperature of the first drying treatment in step (1) is 50-70°C, for example, 50°C, 54°C, 58°C, 62°C, 66°C or 70°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] In the present invention, the end point of the first drying treatment is to provide a water-free environment for the metal mesh film, thereby providing a basis for the subsequent calcination of the metal mesh film. The present invention provides the mesh film with a rough structure through the first calcination treatment described in step (1), thereby facilitating the TiO 2 The loading of the sol improves the separation efficiency; when the temperature of the first calcination treatment increases or decreases, it will make it difficult to form a rough surface morphology, which in turn leads to a decrease in the separation efficiency.

[0024] As a preferred technical solution of the present invention, the spin coating time in step (2) is 1 to 3 minutes, for example, it can be 1 minute, 1.4 minutes, 1.8 minutes, 2.2 minutes, 2.6 minutes or 3 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] Preferably, the spin coating speed in step (2) is 450-550 r / min, for example, it can be 450 r / min, 470 r / min, 490 r / min, 510 r / min, 530 r / min or 550 r / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, in step (2), the TiO 2 The concentration of the sol is 6-18wt%, for example, 6wt%, 9wt%, 12wt%, 15wt% or 18wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] In the present invention, by regulating the TiO 2 The concentration of the sol and the spin coating time are used to adjust the TiO coating on the base film. 2 TiO 2 When TiO 2 When the coating thickness increases, the rough surface morphology will be caused by the thicker TiO 2 masking, thereby reducing the separation efficiency.

[0028] In the present invention, the TiO 2The preparation method of the sol comprises: mixing deionized water, HCl and polyethylene glycol 400 in an ethanol (EtOH) solution of tetrabutyl titanate (TBOT), and then performing vigorous stirring and aging treatment for 24 hours in sequence to obtain the TiO 2 Sol.

[0029] Preferably, when the TiO 2 When the concentration of the sol is 6wt%, the TiO 2 The molar ratio of tetrabutyl titanate, ethanol, deionized water, HCl and polyethylene glycol 400 in the sol is 1:12.2:2.5:0.08:0.1.

[0030] As a preferred technical solution of the present invention, the temperature of the second drying treatment in step (2) is 60-130°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or 130°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the time for the second drying treatment in step (2) is 6 to 18 hours, for example, it can be 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours or 18 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] As a preferred technical solution of the present invention, the temperature of the second calcination treatment in step (2) is 350-450°C, for example, it can be 350°C, 370°C, 390°C, 410°C, 430°C or 450°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the time of the second calcination treatment in step (2) is 2 to 6 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] In the present invention, the second drying process is used to remove the TiO 2 The purpose of the second calcination treatment is to make TiO 2 The sol removes chemically bonded water and transforms into TiO with good crystal form. 2 When the temperature or time in the second calcination treatment is too high (excessive calcination), the obtained TiO 2 -The metal mesh composite membrane cracks due to high temperature, which in turn affects the membrane's bonding strength and oil-water separation effect.

[0035] As a preferred technical solution of the present invention, the alkali solution in step (3) includes sodium hydroxide solution and / or potassium hydroxide solution.

[0036] Preferably, the concentration of the alkali solution in step (3) is 8 to 12 mol / L, for example, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] As a preferred technical solution of the present invention, the temperature of the hydrothermal modification treatment in step (3) is 100-200°C, for example, it can be 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, the time of the hydrothermal modification treatment in step (3) is 8 to 16 hours, for example, it can be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] In the present invention, the hydrothermal modification treatment described in step (3) can make TiO 2 -The metal mesh composite membrane has good demulsification ability, which further improves the separation effect of oil-water mixture.

[0040] In addition, when the hydrothermal modification treatment time is too long, it will cause TiO 2 The stacking structure of the sheets is too dense, which weakens the binding force and reduces the oil-water separation flux; if the treatment time is too short, it will cause TiO 2 The stacking structure of the sheets is too loose, which is not conducive to improving the oil-water separation efficiency.

[0041] As a preferred technical solution of the present invention, the method for preparing a super hydrophilic oil-water separation membrane provided in the first aspect of the present invention comprises the following steps:

[0042] (1) subjecting the metal mesh membrane to a cleaning treatment, a first drying treatment, and a first calcination treatment in sequence to obtain a membrane base;

[0043] The pore size of the metal mesh is 200-600 mesh; the temperature of the first calcination treatment is 700-800°C and the time is 4-8h;

[0044] (2) TiO 2 The sol is spin-coated on the film base obtained in step (1), and then subjected to a second drying treatment and a second calcination treatment to obtain TiO 2 -Metal mesh composite film;

[0045] The spin coating time is 1 to 3 minutes, and the rotation speed is 450 to 550 r / min; the TiO 2 The concentration of the sol is 6 to 18 wt %;

[0046] The temperature of the second drying treatment is 60-130°C and the time is 6-18 hours; the temperature of the second calcination treatment is 350-450°C and the time is 2-6 hours;

[0047] (3) The TiO obtained in step (2) 2 - The metal mesh composite membrane is immersed in an alkali solution with a concentration of 8 to 12 mol / L for hydrothermal modification, and the super-hydrophilic oil-water separation membrane is obtained after cleaning;

[0048] The temperature of the hydrothermal modification treatment is 100-200° C., and the time is 8-16 hours.

[0049] In a second aspect, the present invention provides a super-hydrophilic oil-water separation membrane, which is obtained by the preparation method provided in the first aspect.

[0050] It is worth noting that the superhydrophilic oil-water separation membrane provided by the present invention has a pipeline array structure, and its thickness is 3 to 5 μm, for example, it can be 3 μm, 3.4 μm, 3.8 μm, 4.2 μm, 4.6 μm or 5 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0051] In a third aspect, the present invention provides an application of a super-hydrophilic oil-water separation membrane obtained by the preparation method provided in the first aspect, wherein the super-hydrophilic oil-water separation membrane is used to separate an oil-water mixture.

[0052] The particle size of the oil in the oil-water mixture is 0.1 to 100 μm, for example, 0.1 μm, 10 μm, 30 μm, 50 μm, 70 μm or 100 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0053] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] (1) The super-hydrophilic oil-water separation membrane provided by the present invention has super-hydrophilic and super-oleophobic properties and good demulsification function, and can effectively separate the emulsified oil in the oil-water mixture;

[0056] (2) The super-hydrophilic oil-water separation membrane provided by the present invention has good chemical stability and mechanical stability and can operate stably for a long time under different environmental conditions;

[0057] (3) The preparation method provided by the present invention combines physical and chemical methods, is simple to operate, does not require the addition of additional chemical reagents, is environmentally friendly, and has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 A scanning electron microscope image of the super-hydrophilic oil-water separation membrane provided in Example 1 of the present invention;

[0059] Figure 2 Schematic diagram of the content of emulsified oil in emulsion oil-water when separation is performed using different separation membranes. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0061] Example 1

[0062] This embodiment provides a super-hydrophilic oil-water separation membrane, and the preparation method of the super-hydrophilic oil-water separation membrane comprises the following steps:

[0063] (1) subjecting a stainless steel mesh membrane to a cleaning treatment, a first drying treatment, and a first calcination treatment in sequence to obtain a membrane base;

[0064] The pore size of the stainless steel mesh is 600 mesh; the temperature of the first calcination treatment is 800°C and the time is 6 hours;

[0065] (2) TiO 2 The sol is spin-coated on the film base obtained in step (1), and then subjected to a second drying treatment and a second calcination treatment to obtain TiO 2 -Metal mesh composite film;

[0066] The spin coating time is 1 min, the rotation speed is 500 r / min; the TiO 2 The concentration of the sol is 6wt%;

[0067] The temperature of the second drying treatment is 120°C and the time is 12h; the temperature of the second calcination treatment is 400°C and the time is 2h;

[0068] (3) The TiO obtained in step (2) 2 - The metal mesh composite membrane is immersed in a sodium hydroxide solution with a concentration of 10 mol / L for hydrothermal modification, and the super-hydrophilic oil-water separation membrane is obtained after cleaning;

[0069] The temperature of the hydrothermal modification treatment is 150° C. and the time is 12 hours.

[0070] The scanning electron microscope image of the super hydrophilic oil-water separation membrane provided in this embodiment is as follows: Figure 1 As shown, according to Figure 1 It can be seen that the super-hydrophilic oil-water separation membrane provided by the present invention has a neat pipeline array structure.

[0071] Example 2

[0072] This embodiment provides a super-hydrophilic oil-water separation membrane, and the preparation method of the super-hydrophilic oil-water separation membrane comprises the following steps:

[0073] (1) subjecting the titanium mesh membrane to a cleaning treatment, a first drying treatment, and a first calcination treatment in sequence to obtain a membrane base;

[0074] The pore size of the titanium mesh membrane is 200 mesh; the temperature of the first calcination treatment is 700° C. and the time is 8 hours;

[0075] (2) TiO 2 The sol is spin-coated on the film base obtained in step (1), and then subjected to a second drying treatment and a second calcination treatment to obtain TiO 2 -Metal mesh composite film;

[0076] The spin coating time is 3 min, the rotation speed is 450 r / min; the TiO 2 The concentration of the sol is 18 wt%;

[0077] The temperature of the second drying treatment is 60°C and the time is 18 hours; the temperature of the second calcination treatment is 350°C and the time is 6 hours;

[0078] (3) The TiO obtained in step (2) 2 - The metal mesh composite membrane is immersed in a sodium hydroxide solution with a concentration of 8 mol / L for hydrothermal modification, and the super-hydrophilic oil-water separation membrane is obtained after cleaning;

[0079] The temperature of the hydrothermal modification treatment is 200° C. and the time is 8 hours.

[0080] Example 3

[0081] This embodiment provides a super-hydrophilic oil-water separation membrane, and the preparation method of the super-hydrophilic oil-water separation membrane comprises the following steps:

[0082] (1) subjecting the copper mesh membrane to a cleaning treatment, a first drying treatment, and a first calcination treatment in sequence to obtain a membrane base;

[0083] The pore size of the copper mesh membrane is 400 mesh; the temperature of the first calcination treatment is 750° C. and the time is 8 hours;

[0084] (2) TiO 2 The sol is spin-coated on the film base obtained in step (1), and then subjected to a second drying treatment and a second calcination treatment to obtain TiO 2 -Metal mesh composite film;

[0085] The spin coating time is 2 min, the rotation speed is 550 r / min; the TiO 2 The concentration of the sol is 12 wt%;

[0086] The temperature of the second drying treatment is 130°C and the time is 6 hours; the temperature of the second calcination treatment is 450°C and the time is 4 hours;

[0087] (3) The TiO obtained in step (2) 2 - The metal mesh composite membrane is immersed in a potassium hydroxide solution with a concentration of 12 mol / L for hydrothermal modification, and the super-hydrophilic oil-water separation membrane is obtained after cleaning;

[0088] The temperature of the hydrothermal modification treatment is 100° C. and the time is 16 hours.

[0089] Example 4

[0090] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0091] In this embodiment, the pore size of the stainless steel mesh membrane in step (1) is adjusted to 100 mesh.

[0092] Example 5

[0093] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0094] In this embodiment, the pore size of the stainless steel mesh membrane in step (1) is adjusted to 800 mesh.

[0095] Example 6

[0096] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0097] In this embodiment, the time of the first calcination treatment in step (1) is adjusted to 2 hours.

[0098] Example 7

[0099] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0100] In this embodiment, the time of the first calcination treatment in step (1) is adjusted to 10 hours.

[0101] Example 8

[0102] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0103] In this embodiment, the TiO 2 The sol spin coating time was adjusted to 4 min.

[0104] Example 9

[0105] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0106] In this embodiment, the TiO 2 The sol spin coating time was adjusted to 0.5 min.

[0107] Example 10

[0108] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0109] In this embodiment, the TiO 2 The concentration of the sol was adjusted to 5 wt %.

[0110] Embodiment 11

[0111] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0112] In this embodiment, the TiO 2 The concentration of the sol was adjusted to 20 wt %.

[0113] Example 12

[0114] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0115] In this embodiment, the time of the hydrothermal modification treatment in step (3) is adjusted to 4 hours.

[0116] Embodiment 13

[0117] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0118] In this embodiment, the time of the hydrothermal modification treatment in step (3) is adjusted to 18 hours.

[0119] Embodiment 14

[0120] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0121] In this embodiment, the concentration of the sodium hydroxide solution in step (3) is adjusted to 5 mol / L.

[0122] Embodiment 15

[0123] This embodiment provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Embodiment 1 only in that:

[0124] In this embodiment, the concentration of the sodium hydroxide solution in step (3) is adjusted to 18 mol / L.

[0125] Comparative Example 1

[0126] This comparative example provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Example 1 only in that:

[0127] In this comparative example, step (1) the first calcination process was omitted.

[0128] Comparative Example 2

[0129] This comparative example provides a super-hydrophilic oil-water separation membrane. The preparation method of the super-hydrophilic oil-water separation membrane is different from that of Example 1 only in that:

[0130] In this comparative example, the hydrothermal modification process described in step (3) was omitted.

[0131] Performance testing:

[0132] The super-hydrophilic oil-water separation membranes provided in the above embodiments and comparative examples were used to carry out an emulsion oil-water separation test, and the results are shown in Table 1.

[0133] The preparation method of the emulsion oil-water comprises: mixing 1g peanut oil and 0.1g Span80 (sorbitan monooleate) in 1L deionized water, and stirring magnetically for 1h to obtain a stable water-in-oil emulsion system;

[0134] The emulsion oil-water separation test method comprises: after wetting the super-hydrophilic oil-water separation membrane, clamping it in two specially made glass flange tubes, first using sealant to ensure that the device does not leak. In the separation test, the prepared emulsion oil-water is directly poured on the super-hydrophilic oil-water separation membrane, and the permeated water is collected to achieve water-through oil-blocking separation. The filtered mesh is soaked in ethanol for washing for 30 minutes, and placed in the air for 5 minutes for standby use.

[0135] Evaluation criteria: The COD (chemical oxygen demand) of the filtered liquid indirectly determines the oil content in the water. The ratio of the difference in COD before and after filtration to the COD of the previous emulsion (i.e., separation efficiency) is used as an evaluation. The higher the separation efficiency, the better the separation performance of the membrane.

[0136] In addition, the membranes provided in Example 1 and Comparative Example 2 were used to separate the oil and water in the emulsion. The schematic diagram of the change of the oil content during the separation process is shown in FIG. Figure 2 As shown;

[0137] Figure 2 In the figure, the black curve represents the emulsion oil-water; the red curve represents the fraction separation process curve using the membrane provided in Comparative Example 2; and the blue curve represents the fraction separation process curve using the membrane provided in Example 1.

[0138] Table 1

[0139] Oil-water mixture separation efficiency (%) <![CDATA[Flux (L·m -2 ·h -1 )]]> Example 1 81 31545 Example 2 67 36368 Example 3 72 32785 Example 4 60 38420 Example 5 77 20124 Example 6 65 32445 Example 7 21 31368 Example 8 77 31594 Example 9 72 31785 Example 10 75 32445 Embodiment 11 77 31364 Example 12 3 37942 Example 13 78 30754 Embodiment 14 73 31132 Embodiment 15 70 31259 Comparative Example 1 52 38264 Comparative Example 2 55 33054

[0140] Comprehensive analysis of Table 1 shows the following points:

[0141] (1) Comprehensive analysis of Examples 1-3 shows that the super-hydrophilic oil-water separation membrane provided by the present invention has a relatively good separation efficiency for emulsified oil, and the separation efficiency is above 65%;

[0142] (2) Comprehensive analysis of Example 1 and Examples 4-5 shows that when the mesh number of the membrane increases, the pore size of the membrane gradually decreases, the flux decreases as the pore size of the membrane decreases, and the separation efficiency increases as the pore size of the membrane increases; when the mesh number of the membrane is too large, the pore size of the membrane is small, which reduces the flux, thereby reducing the permeability of the membrane and increasing the separation time of the membrane; conversely, when the mesh number of the membrane is too small, the pore size of the membrane is large, which increases the flux, thereby reducing the separation time of the membrane, but reduces the separation efficiency of the membrane;

[0143] (3) Comprehensive analysis of Example 1, Examples 6-7 and Comparative Example 1 shows that the calcination process of the membrane base will affect the roughness of the membrane base, thereby affecting the TiO 2 The loading effect of sol;

[0144] When the first calcination treatment time is too long, the membrane will become brittle and easy to break, and the separation efficiency will be significantly reduced. On the contrary, when the first calcination treatment time is too short, it will be difficult to form a rough morphology, resulting in the TiO 2 Adhesion is difficult and separation efficiency is reduced;

[0145] Furthermore, when the membrane substrate is not calcined, the TiO 2 The sol is difficult to load on the surface of the steel mesh, and the lack of rough structure will lead to;

[0146] (4) Comprehensive analysis of Example 1 and Examples 8-11 shows that TiO 2 Sol spin coating time and TiO 2 The sol concentration will affect the TiO 2 The coating thickness;

[0147] When the TiO 2 As the coating thickness increases, the rough surface morphology is covered by the thicker TiO 2 Masking, thereby reducing separation efficiency;

[0148] (5) Comprehensive analysis of Example 1, Examples 12-15 and Comparative Example 2 shows that the hydrothermal modification process will affect the modification effect of the membrane and even affect its demulsification function;

[0149] When the hydrothermal modification treatment time is insufficient, it will lead to the production of linear TiO 2 The structure of the linear TiO 2 The structure has little impact, and the separation efficiency is also small, resulting in a waste of resources;

[0150] If the hydrothermal modification is not performed, the membrane will not have a demulsification structure, and the emulsified oil cannot be separated, resulting in a significant reduction in separation efficiency;

[0151] When the concentration of the alkali solution used in the hydrothermal modification treatment is too high, the growth rate will be too fast, resulting in the formation of TiO 2 The array is easy to fall off, which reduces the separation efficiency; low concentration will lead to slow growth of TiO2, affect the formation of structure, and reduce the separation efficiency;

[0152] (6) According to Figure 2 It can be seen that the TiO 2 -The metal mesh composite membrane cannot separate oil droplets with smaller particle sizes, which further proves that the hydrothermal modification process described in step (3) of the present invention achieves the increase of the demulsification function in the separation membrane, that is, the separation membrane provided by the present invention can effectively process emulsified oil that is difficult to separate.

[0153] In summary, the oil-water separation membrane provided by the present invention has super-hydrophilic and super-oleophobic properties, and can process emulsified oil that is difficult to separate; and the oil-water separation membrane has good chemical stability and mechanical stability, and can operate stably for a long time under different environmental conditions. In addition, the preparation method combines physical and chemical methods, is simple to operate, does not require additional chemical reagents, is environmentally friendly, and has low energy consumption.

[0154] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a super-hydrophilic oil-water separation membrane, characterized in that: The preparation method comprises the following steps: (1) subjecting the metal mesh membrane to a first calcination treatment to obtain a membrane base; (2) spin coating the TiO2 sol on the film substrate obtained in step (1), and then performing a second drying treatment and a second calcination treatment to obtain a TiO2-metal mesh composite film; (3) Immersing the TiO2-metal mesh composite membrane obtained in step (2) in an alkaline solution for hydrothermal modification, and obtaining the super-hydrophilic oil-water separation membrane after cleaning.

2. The method for preparing a super hydrophilic oil-water separation membrane according to claim 1, characterized in that: The metal mesh in step (1) includes any one of a stainless steel mesh, a copper mesh or a titanium mesh, preferably a stainless steel mesh; Preferably, the pore size of the metal mesh in step (1) is 200-600 mesh; Preferably, the temperature of the first calcination treatment in step (1) is 700-800° C.; Preferably, the time for the first calcination treatment in step (1) is 4 to 8 hours.

3. The method for preparing a super hydrophilic oil-water separation membrane according to claim 1 or 2, characterized in that: Step (1) also includes a cleaning treatment and a first drying treatment performed in sequence before the first calcination treatment.

4. The method for preparing a super hydrophilic oil-water separation membrane according to any one of claims 1 to 3, characterized in that: The spin coating time in step (2) is 1 to 3 minutes; Preferably, the spin coating speed in step (2) is 450-550 r / min; Preferably, the concentration of the TiO2 sol in step (2) is 6 to 18 wt%.

5. The method for preparing a super-hydrophilic oil-water separation membrane according to any one of claims 1 to 4, characterized in that: Step (2) The temperature of the second drying treatment is 60 to 130° C. Preferably, the time for the second drying treatment in step (2) is 6 to 18 hours.

6. The method for preparing a super-hydrophilic oil-water separation membrane according to any one of claims 1 to 5, characterized in that: Step (2) The temperature of the second calcination treatment is 350-450° C.; Preferably, the time of the second calcination treatment in step (2) is 2 to 6 hours.

7. The method for preparing a super-hydrophilic oil-water separation membrane according to any one of claims 1 to 6, characterized in that: The alkali solution in step (3) includes sodium hydroxide solution and / or potassium hydroxide solution; Preferably, the concentration of the alkali solution in step (3) is 8 to 12 mol / L; Preferably, the temperature of the hydrothermal modification treatment in step (3) is 100-200°C; Preferably, the hydrothermal modification treatment in step (3) is performed for 8 to 16 hours.

8. The method for preparing a super-hydrophilic oil-water separation membrane according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) subjecting the metal mesh membrane to a cleaning treatment, a first drying treatment, and a first calcination treatment in sequence to obtain a membrane base; The pore size of the metal mesh is 200-600 mesh; the temperature of the first calcination treatment is 700-800°C and the time is 4-8h; (2) spin coating the TiO2 sol on the film substrate obtained in step (1), and then performing a second drying treatment and a second calcination treatment to obtain a TiO2-metal mesh composite film; The spin coating time is 1 to 3 minutes, the rotation speed is 450 to 550 r / min; the concentration of the TiO2 sol is 6 to 18 wt%; The temperature of the second drying treatment is 60-130°C and the time is 6-18 hours; the temperature of the second calcination treatment is 350-450°C and the time is 2-6 hours; (3) immersing the TiO2-metal mesh composite membrane obtained in step (2) in an alkali solution with a concentration of 8 to 12 mol / L for hydrothermal modification, and obtaining the super-hydrophilic oil-water separation membrane after cleaning; The temperature of the hydrothermal modification treatment is 100-200° C., and the time is 8-16 hours.

9. A super-hydrophilic oil-water separation membrane, characterized in that: The super-hydrophilic oil-water separation membrane is obtained by the preparation method described in any one of claims 1-8.

10. An application of the super-hydrophilic oil-water separation membrane as claimed in claim 9, characterized in that: The super-hydrophilic oil-water separation membrane is used to separate oil-water mixture; The particle size of the oil in the oil-water mixture is 0.1-100 μm.

Citation Information

Patent Citations

  • Preparation method of oil-water separation mesh film with super-hydrophilicity and super-lipophobicity

    CN107080975A

  • Wear-resistant super-hydrophilic / underwater super-oleophobic leather collagen fiber membrane as well as preparation and application thereof

    CN115845441A

  • Oil-water separation material, and oil-water separation device and oil-water separation method used for oil-water separation material

    JP2015039685A

  • UV protecting cosmetic composition comprising titania NANO sheet and manufacturing method thereof

    KR1020130089433A